2002
DOI: 10.1046/j.1523-1755.2002.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass and hemodynamic overload in normotensive hemodialysis patients

Abstract: The NTHD patients, without significant pressure and volume overload, still had increased LVM that was partially explained by the persistent flow overload and subclinical LV dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
2
20
0
1
Order By: Relevance
“…Both cohorts demonstrated an increase in LVMi (Figures 2b and 2c) that was not prevented by EPO therapy. These results are consistent with the belief that hemodialysis is a state of hemodynamic and metabolic perturbation which predisposes to LVH (17,33).…”
Section: Discussionsupporting
confidence: 91%
“…Both cohorts demonstrated an increase in LVMi (Figures 2b and 2c) that was not prevented by EPO therapy. These results are consistent with the belief that hemodialysis is a state of hemodynamic and metabolic perturbation which predisposes to LVH (17,33).…”
Section: Discussionsupporting
confidence: 91%
“…13,14 The right common carotid artery diameter at diastole and the intimal-medial thickness of the posterior wall were measured from the 2D echocardiographic images. 11 Various aspects of the function of large arteries were indexed by the trunk pulse wave velocity, 11 aortic compliance (AC), effective arterial elastance (E a ), and carotid augmentation index (AI). 11 AC was the ratio of SV to pulse pressure.…”
Section: Cardiac and Vascular Structure And Functionmentioning
confidence: 99%
“…11 Various aspects of the function of large arteries were indexed by the trunk pulse wave velocity, 11 aortic compliance (AC), effective arterial elastance (E a ), and carotid augmentation index (AI). 11 AC was the ratio of SV to pulse pressure. 15 E a was the ratio of end-systolic pressure (P es ) to SV.…”
Section: Cardiac and Vascular Structure And Functionmentioning
confidence: 99%
“…Consistent with the literature, we also found that LVMI is positively related to PWV. 30,34,35 High aortic PWV is associated with increased aortic stiffness and increased LVH. Covic et al 36 found an open association between aortic stiffness determined by aortic-femoral PWV and LVM.…”
Section: Discussionmentioning
confidence: 99%